Influence of benzoyl peroxide (BPO) on polysiloxane thin films doped with Ce(III) onto tin coated steel and their anticorrosion properties - Da Cruz, F. M. Di L. [UNESP]; Suegama, P. H.; Fugivara, Cecilio Sadao [UNESP]; Santilli, Celso Valentim [UNESP]; Noce, R. D. [UNESP]; Benedetti, Assis Vicente [UNESP] (The Electrochemical Society, 2012)
The influence of benzoyl peroxide (BPO) on the synthesis of polysiloxane thin films doped with Ce(III) deposited onto Sn coated steel as well as their anticorrosion properties are reported. The addition of BPO, whose role is polymerize the film, showed an increase in |Z| values due to the fact that augments the crossed link bonds and therefore improves the protective feature of the film. Ce(III) does not act in the polymerization process and thus is essential the addition of BPO to obtain more resistant polysiloxane films. ©The Electrochemical Society.
Keywords: Anti-corrosion property; Coated steel; Polymerization process; Polysiloxane films; Benzoyl peroxide; Corrosion protection; Corrosion resistance; Thin films; Tin; Silicones